A FLAT-PARALLEL TYPE PHOTOBIOREACTOR DESIGN FOR SEWAGE WATER TREATMENT - Pavliukh , Lesia; Shamanskyi, Sergii; Zaiats , Olga (Science-based technologies, 2021)
Organic and inorganic substances which were released into the environment as a result of domestic, agricultural and industrial water activities lead to organic and inorganic pollution. Effluent is loaded with inorganic nitrogen and phosphorus and causes eutrophication. Microalgae culture offers an interesting step for wastewater treatments, because they provide a tertiary biotreatment coupled with the production of potentially valuable biomass, which can be used for several purposes. Problem statement. The purpose of this article is to develop a photobioreactor design for wastewater treatment in which the application of new elements and connections reduces material consumption for the manufacture of transparent flexible tanks, reducing labor costs for installation and dismantling of tanks, and preventing the mixing of immobilized algae and their removal from the working area of the photobioreactor. Research methodology. Methods were based on a systematic analysis of theoretical research, synthesis, anology and comparison of various photobioreactor designs. Results and discussion. The problem is solved by the fact that the photobioreactor is made in the form of a transparent flowing rectangular open-topped tank. The flowing flat transparent containers, made with flexible material, are vertically, parallel to each other attached to the bottom of the tank with quick-release fasteners inside. Pipelines for supply saturated by carbon dioxide wastewater and microalgae are connected through non-return valves. Pipelines for drainage of a mixture of microalgae with residual wastewater are connected through non-return valves. Pipelines for drainage of treated wastewater and valves for release of accumulated gases are connected in the upper airtight part. The pipeline for the treatment of treated wastewater is connected to the guide tray for supplying treated wastewater in the middle of a flowing rectangular open-topped tank. A carbon dioxide supply pipeline is connected to the inlet part of the wastewater supply pipeline. At the outlet of the pipeline for the removal of a mixture of microalgae with residual wastewater is a separator of microalgae to separate the return and excess biomass to supply separated from microalgae wastewater in a flowing rectangular tank. Conclusions. The proposed construction of photobioreactor can have good perspectives to be use in communal services for sewage water purification from biogenic elements. Improved photobioreactor design also can be used in sewage systems of enterprises of different branches of industry, when it is necessary to purify sewage water. The proposed flat-parallel type photobioreactor design for sewage water treatment differs by changing the geometric shape of the tanks, which serves a mixture of water and microalgae, resulting in a reduction in material costs for the manufacture of tanks and labor costs for their maintenance